READING THE FAR RIGHT BEYOND SELF-RIGHTEOUSNESS: NEOLIBERALISM, DEMOCRATIC DEFICIT, AND JAVIER MILEI'S GLOBAL LEADERSHIP - Paulo Ravecca; Emiliano Robaina; Facundo Zannier (Lua Nova: Revista de Cultura e Política)
Abstract This article is an invitation to reflect on the far right beyond self-righteousness. The authors challenge the conventional perception of the far right as wholly separate from mainstream politics and society, arguing instead that there is substantial overlap, particularly in terms of patriarchy, racism, and neoliberalism. Nonetheless, the right does innovate and evolve, and it is important to make sense of these shifts. The article’s second section argues that some of the most cutting-edge forms of right-wing activism are currently unfolding in the Global South. Argentinian President Javier Milei’s leadership is a noteworthy case, as it blends right-wing intersectionality (Ravecca et al., 2022a; 2022b), a conservative version of the critique of elite capture (O. Táíwò, 2022), and the theological dimension of neoliberalism (Kotsko, 2018). The conclusion goes back to the idea that, at multiple significant levels, there is no pure exteriority between the far right and the rest of us. Even Milei’s ‘new’ rhetoric radicalizes tendencies that were already present in the main corridors of politics and academia.